2022
DOI: 10.3138/canlivj-2022-0001
|View full text |Cite
|
Sign up to set email alerts
|

Real-world treatment patterns, clinical outcomes, and health care resource utilization in advanced unresectable hepatocellular carcinoma

Abstract: BACKGROUND: The incidence of advanced unresectable hepatocellular carcinoma (HCC) is increasing in developed countries and the prognosis of advanced HCC remains poor. Real-world evidence of treatment patterns and outcomes can highlight the unmet clinical need. METHODS: We conducted a retrospective population-based cohort study of advanced unresectable HCC patients diagnosed in Alberta, Canada (2008–2018) using electronic medical records and administrative claims data. A chart review was conducted on patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…Our HCRU results for year 1 of the overall cohort were consistently higher than those reported in Alberta [21]: 1.96 versus 1.05 mean inpatient hospitalizations, 2.85 versus 1.82 mean emergency visits, and 11.65 versus 8.96 mean visits with medical oncologists. This could be attributed to varying practice patterns specific to oncology specialists.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…Our HCRU results for year 1 of the overall cohort were consistently higher than those reported in Alberta [21]: 1.96 versus 1.05 mean inpatient hospitalizations, 2.85 versus 1.82 mean emergency visits, and 11.65 versus 8.96 mean visits with medical oncologists. This could be attributed to varying practice patterns specific to oncology specialists.…”
Section: Discussioncontrasting
confidence: 54%
“…An analysis of 320 HCC patients diagnosed between January 2011 and December 2015 from the Canadian province of Manitoba reported an mOS from diagnosis of approximately 7 months [ 20 ]. Another study examined 1297 advanced unresectable HCC patients in the Canadian province of Alberta and reported an mOS from diagnosis of 12.23 months; however, their patient population included both recurrent and de novo advanced HCC populations [ 21 ]. When examining the mOS of only their de novo population, similar to our study findings, they reported an mOS from diagnosis of less than a year (~10 months) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations